2006
DOI: 10.1002/ijc.21662
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib induces anoikis in human colon carcinoma cells associated with the deregulation of focal adhesions and nuclear translocation of p130Cas

Abstract: Celecoxib, a selective cyclooxygenase-2 (COX-2) inhibitor, is effective as chemopreventive against colon cancer and it is the only nonsteoroidal antiinflammatory drug approved by the FDA for adjuvant therapy in patients with familial adenomatous polyposis. It is also being evaluated, within Phase II and III clinical trials, in combination with standard chemotherapy to treat sporadic colorectal cancer. Nevertheless, its antitumor mechanism of action is still not fully understood. In this study, we have evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 57 publications
4
40
0
Order By: Relevance
“…This finding is consistent with our previous observation that p130Cas overexpression blocks the cytotoxic activity of celecoxib in colon carcinoma cells. 21 Similar observations have been reported in other malignant cells overexpressing p130Cas 9,32 or FAK 33 after different agent exposure. Our finding that most DLBCL patient samples showed expression of at least one of the studied FA proteins indicates that E7123 may be effective in patients.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This finding is consistent with our previous observation that p130Cas overexpression blocks the cytotoxic activity of celecoxib in colon carcinoma cells. 21 Similar observations have been reported in other malignant cells overexpressing p130Cas 9,32 or FAK 33 after different agent exposure. Our finding that most DLBCL patient samples showed expression of at least one of the studied FA proteins indicates that E7123 may be effective in patients.…”
Section: Discussionsupporting
confidence: 78%
“…21 We have also shown that E7123, a celecoxib derivative that does not inhibit COX-2, was more potent than celecoxib in inducing cell death by FA signaling inhibition in acute myeloid leukemia cells. 22 Our aim in this study was to evaluate whether E7123 was effective in DLBCL and determine its mechanism of action.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…4A, row 2). It has been reported that proteolysis of p130Cas is associated with the induction of apoptosis by different agents (etoposide, cisplatin, and celecoxib) and generates a 31-kDa fragment (15,16). This small fragment is translocated to the nucleus where it acts as a transcriptional repressor and leads to anoikis, a type of apoptosis caused by disruption of cell-matrix interactions (17).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been described that p130CAS cleavage may result from over-expression of the chemokine CXCL12 84 and also from the inhibition of activity of cyclooxygenase 2 (COX2), a key enzyme in prostaglandin synthesis that promotes tumour progression and angiogenesis 85 . Treatment of colon cancer cells with the COX2 inhibitor celecoxib induces proteolysis of p130CAS and nuclear translocation of the 31 kDa fragment, which leads to apoptosis 86 . Moreover, in a panel of human acute myeloid leukemia cell lines, the antitumour effect observed upon treatment with celecoxib is due to the inhibition of p130CAS signalling leading to apoptosis 87 .…”
Section: Apoptosismentioning
confidence: 99%